Composting Horse Manure on Small Farms: Managing Your Compost Bins - Erika Sakers; Mary G. Lusk; Carissa Wickens; Caitlin Bainum (EDIS)
This new 5-page publication of the UF/IFAS Department of Soil, Water, and Ecosystem Sciences is the second in a two-part series on composting horse manure on small farms. The purpose of this article is to share some how-to tips on building and managing manure compost bins. This article is intended for noncommercial horse owners. Written by Erika Sakers, Mary G. Lusk, Carissa Wickens, and Caitlin Bainum. https://edis.ifas.ufl.edu/ss710